Exploring Paternal Mentalization Among Fathers of Toddlers Through a Clay-Sculpting Task - Grenimann Bauch, Nehama; Bat Or, Michal (Frontiers in Psychology, 2021)
This study inquired into parental mentalization processes as they unfolded during a sculpting task administered to fathers of toddlers. Parental mentalization- the parent’s ability to understand behavior (his/her own as a parent and that of their child) based on its underlying mental states (Luyten, Nijssens, Fonagy & Mayes, 2017), is considered crucial within parent-child relationships (Fonagy, et al., 1998) and child development (Steele & Steele, 2008). Eleven Israeli first-time fathers (n=11) of children aged two to three (mean = 2.3) were asked to sculpt a representation of themselves with their child using clay. Following the task, the fathers were interviewed while observing the sculpture they had created. Qualitative thematic analysis integrated three types of data – the video footage of the sculpting processes, the sculptures themselves, and transcripts of the post-sculpting interviews. By focusing on data extracts relating to mentalization processes, three main aspects of the clay-sculpting task and interview were identified as processes that either preceded controlled mentalization instances and/or related to their underlying dynamics: (1) Discussing the sculpting process elicited the father’s curiosity and wonder; (2) Observing the sculpture/ sculpting process revealed gaps in paternal representations; (3) The pre-planning of the sculptures sparked nonverbal exploration of metaphors and symbolism. Special attention was given, in the analysis, to the interplay between verbal and nonverbal aspects of mentalization as they appeared in the metaphorical representations that arose through the sculpting process. Comparing this sample to a previous sample of mothers who were given the same task, similarities and differences were explored, with specific reference to topics of embodiment, gender roles, paternity leave, and an active approach in art therapy. The discussion indicates that clay sculpting may offer unique insight into implicit parental mentalization. Possible clinical applications are discussed, with reference to attachment theory and clinical art therapy approaches.